COMPARATIVE ANALYSIS OF THE IMPLEMENTATION OF THE OHS MANAGEMENT SYSTEM AT PT. KHE BENUA SENTOSA WITH STANDARD PP NO. 50 TAHUN 2012. 50 YEAR 2012 - Whydiantoro; Chindi Fariha Tuzahra; Tigor Muhammad (Universitas Majalengka, 2024)
This research analyzes the implementation of the Occupational Health and Safety Management System (OHSMS) at PT. KHE Benua Sentosa, comparing it to the standards established in Indonesia’s Government Regulation No. 50 of 2012. Recognizing the critical role of occupational health and safety (OHS) in promoting a safe work environment and enhancing productivity, this study investigates PT. KHE Benua Sentosa’s adherence to regulatory requirements, focusing on policies, planning, implementation, monitoring, and review mechanisms. Employing a qualitative approach with document analysis, the study evaluates the effectiveness of OHS policies at PT. KHE Benua Sentosa based on company documentation. The results reveal that PT. KHE Benua Sentosa has effectively implemented OHSMS standards in line with PP No. 50 of 2012. Key areas of compliance include risk assessment, regular training, performance audits, and continuous improvements, demonstrating the company’s commitment to regulatory standards and worker safety. These findings highlight the alignment between PT. KHE Benua Sentosa’s practices and national OHS standards, contributing to the broader discourse on effective OHS management in the construction sector.